ANALYSIS OF RISK FACTORS OF SEXUAL TRANSMITTED INFECTIONS - Putra Apriadi Siregar; Fauziah Nasution; Nurhayati Nurhayati; Muhammad Ancha Sitorus; Reni Armayani Nasution; Fitri Hayati (Jurnal Riset Kesehatan, 2021)
Sexually transmitted infections (STIs) are a very dangerous problem, especially with the transmission of STIs. The incidence of STIs is still high because people's knowledge of STIs is still low, and people are still ashamed to admit to STI sufferers so that STI cases are still high. The purpose of this study was to determine the analysis of risk factors of sexually transmitted infections in North Sumatera province (secondary data analysis for the 2017 IDHS). This study conducted a secondary data analysis of the 2017 IDHS in North Sumatra Province. This research was conducted on 1717 women of childbearing age in North Sumatra Province. This study used the Chi-square test and Prevalent Rate (PR). The results of this study show chi-square analysis results showed a relationship between the source for STI knowledge: health professional (p 0.001), knowledge of the source for STI knowledge: a religious institution (p 0.001), male STI symptoms (p 0.001) with sexual transmitted infections symptoms with a p-value 0.001. A woman of childbearing age who has a partner with STI symptoms has a 26.088 times greater risk of suffering from an STI than a woman of childbearing age whose partner does not have STI symptoms. Sexually transmitted infections (STIs) are related to STI knowledge: health professional, knowledge of the source for STI knowledge: a religious institution, male STI symptoms. Symptoms of STIs in women of childbearing age partners are closely related to the incidence of STIs in women of childbearing age.